Incentivizing university students to quit smoking: a randomized controlled trial of a contingency management intervention in a developing country - Hofmeyr, Andre; Kincaid, Harold; Rusch, Olivia (The American journal of drug and alcohol abuse, 2020)
Background: Contingency management (CM) is an empirically supported behavioral treatment for tobacco use, but its efficacy with university student smokers in a developing country is unknown. Objectives: We evaluate a randomized controlled trial of a CM smoking cessation program conducted on a sample of treatment-seeking student smokers at the University of Cape Town. Methods: The study included a recruitment period, a 6-week intervention period, and a 6-month follow-up period. Subjects in the control group (information and monitoring; n = 47, 76% male) were given information to help them quit smoking and had their quit attempt monitored, receiving R50 ($8) at each assessment. Subjects in the treatment group (information and monitoring, plus CM; n = 40, 80% male) could additionally earn R150 ($24) in abstinence-contingent incentives at each assessment. Outcome variables: 7-day point-prevalence abstinence at 6 months and at the end of the intervention period, and a repeated measure of smoking intensity of non-abstinent subjects. Results: CM had no long-term effect on abstinence at 6 months but had a marked and statistically significant effect on the likelihood of abstinence by the end of the intervention period (p < .001). In addition, while CM did not affect smoking intensity, participation in the program decreased the average number of cigarettes smoked per day by non-abstainers (p < .001). Conclusions: The CM program was efficacious in promoting abstinence amongst treatment-seeking university students in a developing country but only while incentives were in place. Future research should focus on promoting continuous abstinence with this target sample.